(untitled) (Journal of Educational Sciences, 2016)
This article is devoted to the problems of designing of the educational ideal in the context, the author of the proposed approach to the analysis of pedagogical reality. The author substantiates the thesis that the design of the educational ideal is determined by the paradigmatic, civilization, information and cultural self-determination of subjects of this process